"Cara inchada" of cattle, an infectious, apparently soil antibiotics-dependant periodontitis in Brazil - Döbereiner,Jürgen (2000)
The objective of this review on the investigation of "cara inchada" in cattle (CI), pursued over the last 30 years, was to elucidate the pathogenicity of the disease and come to proper conclusions on its etiology. CI has been widely considered to be of nutritional origin, caused primarily by mineral deficiency or imbalance. However, the disease consists of a rapidly progressive periodontitis, affecting the periodontal tissues at the level of the premolars and molars during the period of tooth eruption generally starting in young calves. The disease led to great economic losses for farmers in central-western Brazil, after the occupation of new land for cattle raising in the 1960s and 1970s. The lateral enlargement of the maxillary bones of affected calves gave the disease the popular name of "cara inchada", i.e., swollen or enlarged face. The enlargement was found to be due to a chronic ossifying periostitis resulting from the purulent alveolitis of CI. Black-pigmented non-saccharolytic Bacteroides melaninogenicus, always together with Actinomyces (Corynebacterium) pyogenes, were isolated in large numbers from the periodontal lesions. B. melaninogenicus could be isolated in small numbers also from the marginal gingiva of a few healthy calves maintained on CI-free farms. "In vitro"-assays showed that streptomycin and actinomycin, as well as the supernatants of cultivates of actinomycetes from soils of CI-prone farms, applied in subinhibitory concentrations to the bacteria tested, enhanced significantly (up to 10 times) the adherence of the black-pigmented B.melaninogenicus to epithelial cells of the bovine gingiva. The antibiotics are apparently produced in large quantities by the increased number of soil actinomycetes, including the genus Streptomyces, that develop when soil microflora are modified by cultivating virgin forest or "Cerrado" (tree-savanna) for the first time for cattle grazing. The epidemiology of CI now provides strong evidence that the ingestion with the forage of such antibiotics could possibly be an important determinant factor for the onset and development of this infectious periodontitis. The antibiotic enhanced adherence of B.melaninogenicus to the sulcus-epithelium of the marginal gingiva, is thought to allow it to colonize, form a plaque and become pathogenic. There is experimental evidence that this determinant factor for the development of the periodontitis is present also in the milk of the mothers of CI-diseased calves. It has been shown that the bacteria isolated from the periodontal CI-lesions produce enzymes and endotoxins capable of destroying the periodontal tissues. The epidemiology of CI, with its decline in incidence and its disappearance after several years, could be explained by the fact that the former equilibrium of the microflora of the once undisturbed virgin soil has been reached again and that the number of antibiotic producing actinomycetes has been anew reduced. By this reasoning and all the data available, CI should be considered as a multifactorial infectious disease, caused primarily by the anaerobic black-pigmented non-saccharolytic Bacteroides melaninogenicus, always together with the micro-anaerobic Actinomyces pyogenes. Accordingly, the onset and development of the infectious periodontitis is apparently determined by ingestion with the forage of subinhibitory concentrations of antibiotics produced in recently cultivated virgin soils. This hypothesis is supported by the recent observation of renewed outbreaks of CI-periodontitis in former CI-prone areas, following fresh cultivation after many years. The infectious nature of CI is confirmed by trials in which virginiamycin was used efficiently for the oral treatment of CI-diseased cattle. Previously it has been shown, that spiramycin and virginiamycin, used as additives in mineral supplements, prevented CI-periodontitis.